Metal oxides as a biostimulator for upregulation of genes involved in the biosynthesis of Rebaudioside A - Mirzaei, Alireza; Kavoosi, Gholamreza; Dezhsetan, Sara; Behnamian, Mahdi (Cellular and Molecular Biology, 2018)
Stevia rebaudiana Bertoni is a kind of perennial medicinal plant with sweetening properties which belongs to Asteraceae family. Its leaves with fundamental glycoside compounds consist of both a sugar part and a non-sugar sector. One of the glycoside compounds is Rebaudioside A which has a greater importance in business. This experiment was conducted to evaluate the effects of Ag2O, CrO3, PbO, Fe2O3, BaO and TiO2 on the expression pattern of these genes in the Stevia rebaudiana. Rebaudioside A biosynthesis was repeated 3 times with concentrations of 50, 100 and 200µM. Also, the results of the study pertaining to the expression pattern of these genes showed that metal oxides have led to an increase in the expression of the regulatory genes involved in biosynthesis of Rebaudioside A. According to the expression profile, it was found that its effect on DXR, HDS, HDR, IDI and CPPS genes is more than other genes. The peak HPLC indicated for stevioside and Rebaudioside A represents an increase in the production of this active ingredient under the influence of all treatments. In general, the expression profile of these genes and the results of HPLC show that whatever going to the end of the pathway of production of Rebaudioside A, the activity of the enzymes increases under the influence of these treatments, and eventually a greater amount of Rebaudioside A will be produced. This process shows that metal oxides will have a significant effect on the biosynthesis of Rebaudioside A.